2021
DOI: 10.3390/v13040656
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Bacteriophage Resistance in Vibrio alginolyticus Depends on a Complex Metabolic Adaptation Strategy

Abstract: Lytic bacteriophages have been well documented to play a pivotal role in microbial ecology due to their complex interactions with bacterial species, especially in aquatic habitats. Although the use of phages as antimicrobial agents, known as phage therapy, in the aquatic environment has been increasing, recent research has revealed drawbacks due to the development of phage-resistant strains among Gram-negative species. Acquired phage resistance in marine Vibrios has been proven to be a very complicated process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…Bacteriophage-resistant mutants were obtained through an experimental procedure involving overnight exposure to Athena1 at a multiplicity of infection (MOI) of 100 as described in Skliros et al [ 9 ]. Briefly, three separate cultures of V. alginolyticus were grown in LB medium and inoculated with each phage during the exponential phase (OD 600 : ~0.2) at a MOI of 100.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteriophage-resistant mutants were obtained through an experimental procedure involving overnight exposure to Athena1 at a multiplicity of infection (MOI) of 100 as described in Skliros et al [ 9 ]. Briefly, three separate cultures of V. alginolyticus were grown in LB medium and inoculated with each phage during the exponential phase (OD 600 : ~0.2) at a MOI of 100.…”
Section: Methodsmentioning
confidence: 99%
“…The phage-resistant colonies were further propagated by re-plating, and one colony from each plate was selected as a phage-resistant biological replicate and preserved at −80 °C with 20% glycerol for subsequent analysis. For φ St2 bacteriophage, resistant strains developed earlier [ 9 ] were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key component of cellular regulatory system is metabolites produced by bacteria that interacts with the surrounding host microenvironment [ 4 , 5 ]. Several studies have shown that in Staphylococcus aureus and Vibrio alginolyticus , phenotypic changes, including antimicrobial resistance, can be associated with metabolomic reprogramming [ 6 , 7 ]. Antibiotic resistance has been demonstrated to correlate with alterations in bacterial metabolic pathway, such as folate biosynthesis pathway which is associated with changing bacterial susceptibility to antibiotics (phenotypic resistance) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%